Peran Supervisi Pendidikan dalam Meningkatkan Kualitas Pembelajaran Pasca Pandemi Covid-19 - Putri Nur Aisyah; Sarwandi Kasmei; Nury Ana Harahap (STIKes Ibnu Sina Ajibarang, 2024)
The COVID-19 pandemic has brought major challenges to education systems around the world, forcing a sudden shift to online and hybrid learning. This research aims to describe the importance of educational supervision in improving the quality of learning after the Covid-19 pandemic. Educational supervision in improving the quality of learning is the focus of this research. The method used is library research with a qualitative approach by collecting data sourced from books, articles and published research results. The discussion of this research covers various topics, including the concept of educational supervision, the objectives of educational supervision, the implementation of educational supervision, approaches to educational supervision, principles of educational supervision, techniques of educational supervision in improving the quality of learning. The results of this research show that educational supervision Effective learning plays an important role in helping teachers adapt new technology, overcome learning gaps, and support the mental and emotional well-being of teachers and students as an effort to increase learning effectiveness. In addition, this research found that a holistic approach in supervision, which considers physical and emotional aspects , and social, are critical to creating a learning environment that is inclusive and supports students' holistic development.